Biotic controls of plant coexistence. (13th August 2018) - Bartomeus, Ignasi; Godoy, Oscar
Abstract: The quest for understanding the maintenance of species diversity has matured in recent decades under the umbrella of species coexistence theory, founded by Chesson (2000). The central conclusion of the theory is that coexistence at local scales depends on two opposing forces: average fitness differences between species, which drive the best‐adapted species to exclude others, and stabilizing mechanisms, which promote diversity via niche differentiation. Recent theoretical work has focussed on how interactions between plants and other organisms influence the equalizing and stabilizing forces. However, there is a lack of empirical information. Therefore, the next fundamental step is to assess the prevalence of these mechanisms for controlling plant coexistence across a wide range of interactions and systems. To that end, this special feature presents 10 theoretical, observational, or manipulative studies illustrating 9 different biotic interactions including mutualisms (pollinators, seed dispersers, soil microbes, and arbuscular mycorrhizal fungi) and antagonisms (leaf and seed herbivores, and leaf and root pathogens). All studies share a common question: how biotic interactions regulate plant coexistence? Comparisons across studies suggest that biotic interactions modify both stabilizing and average fitness differences. In those cases where biotic interactions promote stable coexistence between plant species, both mutualistic and antagonistic interactions act more frequently as an equalizing rather than as a stabilizing mechanisms. Besides these generalities, the studies of this special issue also present novel theoretical and empirical approaches to better understand the maintenance of species diversity over a wide variety of systems, environmental conditions, and organisms. Synthesis. The studies presented here constitutes a solid base to empirically explore how mutualistic and antagonistic interactions act upon the determinants of plant species competition, and open novel paths for future research. Collectively, these advances will serve to pave the road for a better theoretical and empirical understanding of how biotic interactions control biodiversity.